Electrode Size and Dimensional Ratio Effect on the Resonant Characteristics of Piezoelectric Ceramic Disk - Wu, Lang; Chure, Ming-Cheng; Chen, Yeong-Chin; Wu, King-Kung; Chen, Bing-Huei (IntechOpen, 2012)
None